Corporate social marketing and brand equity – a case of dairy products in Vietnam - Thi Quy Vo; Tuan Nguyen-Anh (Cogent Business & Management, 2024)
The research conducted to study the impact of customers' perceptions of corporate social marketing (CSM) on the multidimensions of brand equity in the case of dairy products in Vietnam. Research data was collected, through direct interviews, from 780 valid questionnaires responsed by customers living in Ho Chi Minh City and Ha Noi. The study found that CSM is an important factor in brand equity creation, and more effective than distribution intensity and advertising in building a dairy product brand. The results confirm that CSM initiatives positively effect on the five CBBE dimensions (brand awareness, brand associations, perceived quality, brand trust, and brand loyalty) and show causal order among the CBBE dimensions. Futhermore, the research findings enrich the theory of CSM and brand equity and support the Theory of Planned Behavior.
Keywords: 650; corporate social marketing; brand equity; dairy products; Vietnam